A corner store intervention to improve access to fruits and vegetables in two Latino communities. Issue 12 (5th June 2017) - Albert, Stephanie L; Langellier, Brent A; Sharif, Mienah Z; Chan-Golston, Alec M; Prelip, Michael L; Elena Garcia, Rosa; Glik, Deborah C; Belin, Thomas R; Brookmeyer, Ron; Ortega, Alexander N
Abstract: Objective: Investments have been made to alter the food environment of neighbourhoods that have a disproportionate number of unhealthy food venues. Corner store conversions are one strategy to increase access to fruits and vegetables (F&V). Although the literature shows modest success, the effectiveness of these interventions remains equivocal. The present paper reports on the evaluation of Proyecto MercadoFRESCO, a corner store conversion intervention in two Latino communities. Design: A repeated cross-sectional design was employed. Data were stratified by intervention arm and bivariate tests assessed changes over time. Logistic and multiple regression models with intervention arm, time and the interaction of intervention and time were conducted. Supplementary analyses account for clustering of patrons within stores and staggering of store conversions. Setting: Three stores were converted and five stores served as comparisons in East Los Angeles and Boyle Heights, California, USA. Subjects: Store patrons were interviewed before ( n 550) and after ( n 407) the intervention. Results: Relative to patrons of comparison stores, patrons of intervention stores demonstrated more favourable perceptions of corner stores and increased purchasing of F&V during that store visit. Changes were not detected in store patronage, percentage of weekly dollars spent on food for F&V or daily consumption of F&V. Conclusions: Consistent with some extant food environment literature, findings demonstrate limited effects. Investments should be made in multilevel, comprehensive interventions that target a variety retail food outlets rather than focusing on corner stores exclusively. Complementary policies limiting the availability, affordability and marketing of energy-dense, nutrient-poor foods should also be pursued.